The relationship between corporate social responsibility disclosure and executive compensation in listed firms in Malaysia / Nooraisah Katmon ... [et al.] - Katmon, Nooraisah; Hanifa, Mohamed Hisham; Rambeli, Norimah; Mohamad, Zam Zuriyati; Ahamad Rapani, Nor Hanani; Al Farooque, Omar; Ismail, Rosmini (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
We examined the relationship between Corporate Social Responsibility (CSR) Disclosure and Executive Compensation in listed companies in Malaysia. This topic is particularly important since both CSR and Executive Compensation disclosure decisions are subject to managerial discretion, thus the motive of the such disclosure by the firms might potentially be influenced by personal agenda. CSR was measured using the CSR Disclosure Index, while Executive Compensation was measured following the MCCG (2021). We used a panel data of 200 non-financial listed firms during the year 2009-2015. We found that CSR was insignificant in influencing the level of executive compensation in Malaysia. This finding suggests that any changes in CSR will not have an effect on compensation. The unconstructive environment in the emerging economy leads to the manipulation of CSR disclosure, hence weakening its function and effectiveness. We found that firm's profitability positively influenced the level of executive compensation, hence suggesting that a firm's governance system in Malaysia has been strengthened and improved. This study provides useful insights to policy makers in Malaysia in increasing the reliability of CSR and executive compensation, that will benefit the firms as well as the decision makers.